BLENDED LEARNING APPROACHES IN TEACHING ENGLISH AT MILITARY ACADEMIC LYCEUMS - Dadaboyeva Fayyoza Khikmatulloyevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the application of blended learning models in teaching  English  at  military  academic  lyceums.  Combining  traditional  face-to-face instruction  with  digital  tools,  blended  learning  offers  a  flexible,  learner-centered approach that is especially effective in structured and disciplined environments like military institutions. The article discusses the benefits, challenges, and best practices of  implementing  blended  learning  for  English  as  a  Second  Language  (ESL), highlighting its impact on language proficiency, learner autonomy, and operational communication  skills.  Emphasis  is  placed  on  the  need  for  curriculum  adaptation, teacher training, and integration of military-specific content within ESL instruction.